CCAFS science supports Ghana's steps towards climate-resilient cocoa production for 800,000 farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The Ghanaian cocoa sector under the leadership of the Ghanaian Cocoa Board (COCOBOD) made important strides towards climate resilience. Exposure maps developed jointly with CCAFS were combined with exposure gradient specific climate-smart agriculture practices in a national training manual of obligatory use for all public and private extension targeting the 800,000 cocoa farmers in the country.